Knowledge and perspectives of the new National Cervical Screening Program: a qualitative interview study of North Queensland women—‘I could be that one percent’ - Jennifer Banks; Clare Heal; Archana Nagendiram; Rachel Bidgood (BMJ Open)
Objectives To investigate women’s understanding and attitudes towards the National Cervical Screening Program (NCSP) and to explore methods to improve screening participation.Design Semi-structured face-to-face interviews were conducted through convenience and snowball sampling. Thematic analysis occurred using the interpretivist framework.Setting A private general practice in North Queensland.Participants Women between the ages of 18 and 74 who attended the general practice were eligible to participate. Fourteen women between 20 and 58 years old were interviewed.Results Participants were concerned that the new NCSP would miss cancer due to longer screening intervals and reliance on primary human papilloma virus (HPV) testing. They believed that young women are at increased risk of cervical cancer, due to perceived HPV vaccine ineffectiveness and parent objection to vaccination. Most participants were not agreeable to self-sampling and preferred their doctor to perform screening. Personal and practitioner beliefs influenced a woman’s screening participation. Personal factors include being healthy for themselves and their family, previous abnormal smears and family history of cancer. Emphasis was placed on feeling ‘comfortable’ with their practitioner which included patient rapport and gender preference. Proposed methods to improve cervical screening included education programmes, advertising campaigns, general practitioner interventions and improving accessibility.Conclusions It is apparent that women are hesitant about the new NCSP. However, when provided with additional information they were more amenable to the changes. This highlights the need to improve awareness of cervical screening and the new NCSP.